2012
DOI: 10.1021/ja212020b
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Ritter-Type C–H Amination of Unactivated sp3 Carbons

Abstract: Intermolecular Ritter-type C–H amination of unactivated sp3 carbons has been developed. This new reaction proceeds under mild conditions using readily available reagents and an inexpensive source of nitrogen (acetonitrile). A broad scope of substrates can be aminated with this method since many functional groups are tolerated. This reaction also allows for the direct, innate C–H amination of a variety of hydrocarbons such as cyclohexane without the need of prefunctionalization or installation of a directing gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
140
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(150 citation statements)
references
References 58 publications
8
140
0
2
Order By: Relevance
“…The reaction was strictly stereoselective and formed the pure ketoamide with both the methyl and isopropylamide in equatorial positions. The properties of synthesized 2 agreed with the literature for 2 prepared via intermolecular Ritter-type C-H amination of menthone [3].Resonances in the PMR spectrum of 2 could not be fully assigned because of the mutual overlap of many of them. Nevertheless, the following conclusions could be drawn based on the spectrum.…”
supporting
confidence: 78%
“…The reaction was strictly stereoselective and formed the pure ketoamide with both the methyl and isopropylamide in equatorial positions. The properties of synthesized 2 agreed with the literature for 2 prepared via intermolecular Ritter-type C-H amination of menthone [3].Resonances in the PMR spectrum of 2 could not be fully assigned because of the mutual overlap of many of them. Nevertheless, the following conclusions could be drawn based on the spectrum.…”
supporting
confidence: 78%
“…In addition to the issue of selectivity, there are more challenges toward the direct functionalization of sp 3 C-H bonds, including: their high bond dissociation energy, inaccessibility of the independent C-H bonding and antibonding orbitals as well as steric hindrance. In the past decades, great progress has been made in such fields to convert aliphatic sp 3 C-H bonds to C-C, C-O and C-B bonds in either stoichiometric or catalytic manner based on transition-metal catalysis [9][10][11][12][13][14][15] . The present article focuses on the direct amination of inert C sp3 -H bonds, especially primary C-H bonds to construct aza-heterocycles.…”
mentioning
confidence: 99%
“…heating and/or the presence of a strong oxidant such as N-fluoro-N′-(chloromethyl)-triethylenediamine pentafluoro phosphate (F-TEDA-PF 6 ) or ceric ammonium nitrate. [30][31][32][33] We found that 36b could be successfully aminated under mild conditions in CH 3 CN to afford 2,2,2-trifluoroethylether 39 in 49% yield using 35. These reactions may proceed via a carbocation intermediate generated by a two-electron oxidation process.…”
Section: Radical Catalystsmentioning
confidence: 92%